Stayin' alive? Government support measures in Portugal during the Covid-19 pandemic - Márcio Mateus; Katja Neugebauer (Portuguese Economic Journal, 2025)
During the Covid-19 crisis, the Portuguese government has provided a plethora of different support measures for firms. These included state-guaranteed loans and a public moratorium for existing loans. This paper examines the access to and uptake of these measures. What were the characteristics of firms being granted state-guaranteed loans? Were they different for firms accessing the moratorium? Did state-guaranteed loans potentially lead to an increase in zombie lending? We try to answer these questions using highly granular bank-, firm- and loan-level data for Portugal. We find that guaranteed loans went mostly to firms operating in the sectors most severely hit by the pandemic and to firms that previously had a credit relation and/or benefitted from a state guarantee. Furthermore, the Portuguese public guarantee scheme seems to mainly have supported lower-credit-risk firms. In addition to that, riskier firms also paid higher interest rates and obtained smaller guaranteed loans than more viable firms. However, in contrast to our results for the state guarantees, we find that riskier firms were more likely to benefit from the public moratorium.
Keywords: G30; G38; G21; 330; Zombie lending; Zombie firms; Credit misallocation; Evergreening; State aid